Refracted modernity : visual culture and identity in colonial Taiwan - Kikuchi, Yūko (University of Hawaii Press, 2007)
Since the mid-1990s Taiwanese artists have been responsible for shaping much of the international contemporary art scene, yet studies on modern Taiwanese art published outside of Taiwan are scarce. The nine essays collected here present different perspectives on Taiwanese visual culture and landscape during the Japanese colonial period (1895-1945), focusing variously on travel writings, Western and Japanese/Oriental-style paintings, architecture, aboriginal material culture, and crafts. Issues addressed include the imagined Taiwan and the "discovery" of the Taiwanese landscape, which developed into the imperial ideology of nangoku (southern country); the problematic idea of "local color," which was imposed by Japanese, and its relation to the "nativism" that was embraced by Taiwanese; the gendered modernity exemplified in the representation of Chinese/Taiwanese women; and the development of Taiwanese artifacts and crafts from colonial to postcolonial times, from their discovery, estheticization, and industrialization to their commodification by both the colonizers and the colonized. Contributors: Chao-Ching Fu, Chia-yu Hu, Yuko Kikuchi, Kaoru Kojima, Ming-chu Lai, Hsin-tien Liao, Naoko Shimazu, Toshio Watanabe, Chuan-ying Yen